A Survey on Students’ Perception Towards Netflix Application in Speaking Class of the 11th Grade of SMK PGRI 2 Kediri - Fadilla, Diana Nur; Sulistyani; Khoiriyah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This study examines students' perceptions of the use of the Netflix application in English classes, driven by low speaking skills among students, including lack of confidence, limited vocabulary, and difficulty understanding native speakers. This study was conducted at SMK PGRI 2 Kediri with 86 grade XI students using a quantitative approach and survey method. The tool used was a closed-ended questionnaire focusing on four indicators of speaking skills: pronunciation, fluency, accuracy, and performance. The results showed that most students had a positive perception of using Netflix as a learning medium. More than 77% agreed that Netflix improved their pronunciation and fluency, while 90% agreed that it improved their grammatical accuracy. However, only 6% strongly agreed, and 66% of students agreed in terms of performance. It means that it improves their speaking performance, indicating challenges in expressing themselves confidently and with appropriate body language. Netflix's authentic content, such as films and series with subtitles, provides real-life examples of language use, helping students mimic native speaker pronunciation, understand sentence structure, and expand their vocabulary. Despite its limitations, such as the need for active practice outside of watching, Netflix is considered an effective tool for supporting more engaging, flexible, and contextual speaking development. In conclusion, the Netflix app receives positive feedback for helping students improve their speaking skills. Additionally, Netflix can serve as a strong supplementary medium in English-speaking classes, especially when integrated with interactive learning strategies such as role-playing or shadowing.